Movement patterns and player load: insights from professional padel - Miralles, Ricardo; Martínez-Gallego, Rafael; Guzmán, José; Ramón-Llin, Jesús (Biology of Sport, 2025)
Quantifying competition load with kinematic variables from inertial devices provides critical insights into player performance, a practice well adopted especially in team sports. This study aimed to analyse load variables in elite padel players, distinguishing between match winners and losers. Data were collected from 83 players across 23 professional circuit matches. The results highlighted specific load metrics such as distance covered, accelerations and decelerations per hour, peak speeds, and an acceleration profile per distance covered, revealing that winners exhibited significantly higher mobility than losers. Specifically, match winners travelled a greater distance per hour than match losers (Mdn Winners = 2518; Mdn Losers = 2339 m; p = 0.02; r = 0.25) and performed a greater number of accelerations per hour (Mdn Winners = 415; Mdn Losers = 382; p = 0.04; r = 0.22). These findings introduce novel data to padel, promising to refine training adjustments and offer an objective performance evaluation in both training and competitive contexts. The study’s outcomes emphasize the role of mobility in winning matches, suggesting that higher movement and acceleration rates are advantageous. This research fills a gap in padel literature, providing a foundation for future investigations into training and performance optimization strategies.